Air pollution and development in Africa: impacts on health, the economy, and human capital. Issue 10 (October 2021) - Fisher, Samantha; Bellinger, David C; Cropper, Maureen L; Kumar, Pushpam; Binagwaho, Agnes; Koudenoukpo, Juliette Biao; Park, Yongjoon; Taghian, Gabriella; Landrigan, Philip J
Summary: Background: Africa is undergoing both an environmental and an epidemiological transition. Household air pollution is the predominant form of air pollution, but it is declining, whereas ambient air pollution is increasing. We aimed to quantify how air pollution is affecting health, human capital, and the economy across Africa, with a particular focus on Ethiopia, Ghana, and Rwanda. Methods: Data on household and ambient air pollution were from WHO Global Health Observatory, and data on morbidity and mortality were from the 2019 Global Burden of Disease Study. We estimated economic output lost due to air pollution-related disease by country, with use of labour income per worker, adjusted by the probability that a person (of a given age) was working. Losses were expressed in 2019 international dollars and as a proportion of gross domestic product (GDP). We also quantified the contribution of particulate matter (PM)2·5 pollution to intelligence quotient (IQ) loss in children younger than 10 years, with use of an exposure–response coefficient based on previously published data. Findings: Air pollution was responsible for 1·1 million deaths across Africa in 2019. Household air pollution accounted for 697 000 deaths and ambient air pollution for 394 000. Ambient air pollution-related deaths increased from 361 000 in 2015, to 383 000 in 2019, with the greatest increases in the most highly developed countries. The majority of deaths due to ambient air pollution are caused by non-communicable diseases. The loss in economic output in 2019 due to air pollution-related morbidity and mortality was $3·02 billion in Ethiopia (1·16% of GDP), $1·63 billion in Ghana (0·95% of GDP), and $349 million in Rwanda (1·19% of GDP). PM2·5 pollution was estimated to be responsible for 1·96 billion lost IQ points in African children in 2019. Interpretation: Ambient air pollution is increasing across Africa. In the absence of deliberate intervention, it will increase morbidity and mortality, diminish economic productivity, impair human capital formation, and undercut development. Because most African countries are still early in development, they have opportunities to transition rapidly to wind and solar energy, avoiding a reliance on fossil fuel-based economies and minimising pollution. Funding: UN Environment Programme.